2020
DOI: 10.1200/jco.2020.38.15_suppl.6073
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism in patients receiving neoadjuvant chemotherapy for ovarian cancer.

Abstract: 6073 Background: To identify the incidence of newly occurring venous thromboembolism (VTE) in patients with ovarian cancer receiving neoadjuvant chemotherapy (NACT). Methods: Using our prospectively maintained ovarian cancer database, we identified all ovarian cancer patients who received NACT at our institution from 4/15-9/18. VTE events included clinically diagnosed deep venous thrombosis (DVT) or pulmonary embolism (PE). Patients who presented with VTE prior to induction of NACT or patients on anticoagulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous reports have shown that early-onset VTE events are associated with surgery and chemotherapy during treatment of malignant diseases. [14] But, Chavan et al revealed that neoadjuvant chemotherapy was not associated with thromboembolism, and the current combination of commonly used chemotherapeutic agents for ovarian cancer had a minimal risk of thromboembolic events. [15] So how to balance the advantages of neoadjuvant chemotherapy and surgery in OCCC with cerebral infarction and the risks associated with treatment remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that early-onset VTE events are associated with surgery and chemotherapy during treatment of malignant diseases. [14] But, Chavan et al revealed that neoadjuvant chemotherapy was not associated with thromboembolism, and the current combination of commonly used chemotherapeutic agents for ovarian cancer had a minimal risk of thromboembolic events. [15] So how to balance the advantages of neoadjuvant chemotherapy and surgery in OCCC with cerebral infarction and the risks associated with treatment remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of PE occurring after operation or during chemotherapy in patients with ovarian cancer. 3,4 However, con rmed by publicly available niraparib-related treatment adverse events, there have been no reports of PE caused by the use of niraparib in patients with advanced high-grade serous ovarian cancer. Thus, knowledge of the occurrence of PE after the use of niraparib may assist other clinicians in managing this rare but potentially serious toxic effect.…”
Section: Main Textmentioning
confidence: 99%